Understanding Student Academic Fraud: Trends, Causes, and Implications for Higher Education - Sucitra, Intan; Friyatmi (Journal of Educational Management Research, 2025)
Academic cheating behaviour has become a phenomenon that damages the integrity of the world of education; this is due to various supporting factors for academic fraud. This study aimed to analyse students academic fraud behaviour. This is causative quantitative research.  The population in this study is the students; the sample is 200 students. The data was collected using a questionnaire and analysed using descriptive statistics. The results showed that academic fraud behaviour was in the low category, but plagiarism and cheating on exams need special attention. The implications of this study suggest the need for more intensive efforts from the university to raise awareness and address academic cheating behaviors, especially in terms of plagiarism and exam cheating. Academic integrity education programs and stricter policies can help create a more honest and dignified learning environment.